Psychological experiments on the internet - Birnbaum, Michael H. (Academic Press, 2000)
Until recently, most psychological research was conducted using subject samples in close proximity to the investigators--namely university undergraduates. In recent years, however, it has become possible to test people from all over the world by placing experiments on the internet. The number of people using the internet for this purpose is likely to become the main venue for subject pools in coming years. As such, learning about experiments on the internet will be of vital interest to all research psychologists. Psychological Experiments on the Internet is divided into three sections. Section I discusses the history of web experimentation, as well as the advantages, disadvantages, and validity of web-based psychological research. Section II discusses examples of web-based experiments on individual differences and cross-cultural studies. Section III provides readers with the necessary information and techniques for utilizing the internet in their own research designs. * Innovative topic that will capture the imagination of many readers * Includes examples of actual web based experiments.